1.3 V superwide potential window sponsored by Na-Mn-O plates as cathodes towards aqueous rechargeable sodium-ion batteries - Chua, Rodney (2020)
Aqueous rechargeable sodium-ion batteries (ARSIBs) are highly desirable for the large-scale energy storage due to their inherent high safety and low-cost. Na-Mn-O electrode material has been considered as a promising cathode, yet the redox potential window is still not fully explored and utilized in aqueous rechargeable sodium-ion batteries. Herein, a chemical bonded Na0.44MnO2 (NMO) plates are successfully synthesized via a polyvinylpyrrolidone-assisted sol-gel route followed by annealing process. The possibility of utilizing a wider potential window ranging between −0.3 V and 1.0 V vs. Ag/AgCl in mild aqueous electrolyte has been thus demonstrated by using NMO plates as cathodes for the first time. As a result, the as-synthesized NMO plates can deliver a highest initial discharge capacity of 77.2 mA h g−1 at a current density of 100 mA g−1, compared with previous Na-Mn-O reports in mild aqueous electrolyte in ARSIBs. Even at a high rate of 500 mA g−1, it still maintains a large capacity of 35 mA h g−1 after 1000 cycles, demonstrating its superior cycling stability. In addition, ex situ SEM and TEM-EDX results reveal that there is a newly formed sheet-like layer Na-birnessite Na0.55Mn2O4·1.5H2O on the surface of NMO cathodes, which can provide extra ion channel for sodium ions and stabilize the electrode from pulverization, resulting in improved cycling stability. This study provides a broad implication for developing low-cost, high performance cathode materials to broaden the applied potential window towards high performance ARSIBs.